From Left Handed Materials to Invisible Cloak: Recent Advances - Paudyal, Harihar; Johrib, Manoj; Tiwari, Akhilesh (Himalayan Physics, 2013)
Last decade has been increasing interest in metamaterial research, however metamaterials are sometimes regarded as left handed materials (LHM) or negative index materials but the recent progress in the field has shown that metamaterials are far beyond LHMs. In this paper we provide further advancement in the field of structured electromagnetic from LHM to invisible cloak. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 18-26 Uploaded date: 12/22/2013